NEW OPPORTUNITIES TO IDENTIFY AND TYPE STAPHYLOCOCCUS spp. BY USING MALDI-TOF MASS SPECTROMETRY - A. S. Stepanov (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Abstract. Mass spectrometry profiles of microorganisms obtained by time-of-flight matrix-associated laser desorption/ionization (MALDI-TOF) mass spectrometry are a source of information about peptide profiles can be used for microbial identification and typing. A variety of technical and bioinformational solutions complicate developing of a united mass-spectro-profile database. Staphylococcus spp. strains are good studied objects for identification by MALDI-TOF mass spectrometry, frequently resulting in nosocomial infections, especially in immunocompromised patients. Rapid differentiation of nosocomial, multiresistant and highly virulent isolates of Staphylococcus spp. Allows to reduce the lethality in weakened and immunocompromised patients. The study was aimed at assessing comparability and reproducibility of identification and typing results for Staphylococcus spp by MALDI-TOF mass spectrometry. Comparing 292 Staphylococcus spp. isolates in clinical specimens obtained fron the multidisciplinary hospital at the NWSMU im. I.I. Mechnikov was carried out by using MALDI-TOF mass spectrometer BactoSCREEN ID (Litech, Russia) and Bruker Biotyper 3.1 (Bruker GmbH, Germany). Comparability of Staphylococcus spp. identification showed that 95.9%; 12 isolates (4.1%) by “Bruker Biotyper 3.1” and 3 isolates (1.1%) by using “BactoSCREEN ID” were incorrectly identified. Repeated identification leveled the differences between the systems used. In addition, it was shown that the method of protein extraction did not affect reliability of Staphylococcus spp. species identification by using databases (÷2, p > 0.05) compared to intraspecific typing (÷2, p < 0.0001). Using different extraction protocols showed that Staphylococcus spp. mass-spectra differed by peak intensity level within the mass range up to 4000 m/z, 5300±600 m/z and 6500±500 m/z, as well as higher than 7000 m/z. Peaks of low-molecular weight peptides were detected under full protein extraction compared to sample preparation on plate extraction. To develop a unified protocol for mass-spectrometry profile processing, a reliability of the basic statistical variables (mode, median, maximum, minimum and arithmetic mean) was evaluated. Analysis of the median mass spectrometry profiles is recommended for Staphylococcus spp. intraspecific typing by using MALDI-TOF mass spectrometry as the most reproducible and consistent approach. As a result, two systems for MALDI-TOF mass spectrometry reliably identify Staphylococcus spp., but standardization of sample preparation and bioinformation analysis is required for Staphylococcus spp. typing.